Hubungan Pola Struktur Pondasi Dan Ruang Pada Rumah Lama Pekanbaru - Boby Samra (JURNAL TEKNIK UNILAK, 2019)
The old house building in Pekanbaru somehow becomes a part of the city development since it becomes an identity of an old city area. The current population development makes the house grow in line with the needs of space makes the house losing its character and identities. Therefore, it is necessary to conduct a research on to see a dynamic design between the old foundation concrete design and the current needs situation. This current research conducted through a qualitative perspective which consisted several operational method e.g., observation, interview, documentation and discussion. This analysis of the study somehow revealed the shape of space and the structure of the concrete foundation strongly related with the internal room pattern of the house.